Estado actual del mejoramiento del arroz mediante la utilizacion de especies silvestres de arroz en CIAT - Martinez, C.P.=700 1 Thome, J.; Lopez, J.; Borrero, J.; McCouch, S.R.; Roca, W.; Chatel, M.; Guimardes, E.
(Es, En)
ilus., 22 ref.
Keywords: ORYZA SATIVA; GERMOPLASMA; CONSERVACION DEL GERMOPLASMA; ORYZA RUFIPOGON; ORYZA GLABERRIMA; FITOMEJORAMIENTO; MARCADORES GENETICOS; SELECCION; COSTA RICA; ORYZA BARTHII